Un texto mexicano de física del siglo XVIII - Moreno Corral, M.A. (Revista Mexicana de Física E, 2006)
This work introduces one of the first mexican textbooks dealing with physics issues emerging from the Scientific Revolution that took place in the 16th and 17th Centuries. There, concepts of the newtonian mechanics are discussed extensively, particularly Dynamics. Besides, we point out here that the textbook deals with contemporany ideas about electricity being generated in the world. Its author, Ignacio Fernandez del Rincon was one of the first persons in Mexico that carried on experiments with electrostatic machines, with the formel intention to establish a theory about electrical phenomena. He should be considered pioneer of experimental physics in our country.